In vivo sagittal plane kinematics of the FPV patellofemoral replacement. - Monk, A; van Duren, B; Pandit, H; Shakespeare, D; Murray, D; Gill, H (2012)
PURPOSE: Isolated symptomatic patellofemoral osteoarthritis has been reported in 2% of men and 8% of women older than the age of 55 years in the community. With the development of improved designs and surgical techniques, interest in the use of patellofemoral replacement has increased. The primary aim of the newer generation of patellofemoral replacement implant designs has been to more closely reproduce normal knee kinematics. This study compares the functional sagittal plane in vivo kinematics of a contemporary patellofemoral prosthesis, the FPV, with normal knee kinematics using the patella tendon angle and patella flexion angle relationships with the knee flexion angle. METHODS: The in vivo kinematics for a group of 8 patients (15 knees) with patellofemoral replacement and 22 normal subjects was measured for both a step-up and a lunge exercise using an established fluoroscopic method. RESULTS: The patella tendon angle characteristics of the implanted knees were similar to those of the normal knees for the step-up exercise with a significant difference only observed at 50° knee flexion angle. For the lunge exercise, the patella tendon angle for the implanted knee was consistently lower than that measured for the normal knee. Overall the subjects had excellent clinical scores post-patellofemoral replacement showing a significant improvement from their pre-operative scores. CONCLUSION: The kinematics of the FPV implant was closer to normal than those of total knee implants; however, there were still differences from the normal knees. LEVEL OF EVIDENCE: III.